Highly efficient in crystallo energy transduction of light to work - Lin, Jiawei; Zhou, Jianmin; Li, Liang; Tahir, Ibrahim; Wu, Songgu; Naumov, Panče; Gong, Junbo (Nature communications, 2024)
Various mechanical effects have been reported with molecular materials, yet organic crystals capable of multiple dynamic effects are rare, and at present, their performance is worse than some of the common actuators. Here, we report a confluence of different mechanical effects across three polymorphs of an organic crystal that can efficiently convert light into work. Upon photodimerization, acicular crystals of polymorph I display output work densities of about 0.06–3.94 kJ m −3 , comparable to ceramic piezoelectric actuators. Prismatic crystals of the same form exhibit very high work densities of about 1.5–28.5 kJ m −3 , values that are comparable to thermal actuators. Moreover, while crystals of polymorph II roll under the same conditions, crystals of polymorph III are not photochemically reactive; however, they are mechanically flexible. The results demonstrate that multiple and possibly combined mechanical effects can be anticipated even for a simple organic crystal. Crystals are known to have a range of responses to light, but multiple responses in the same material are rare. Here, the authors report different mechanical effects in response to light across three polymorphs as a result of a dimerization reaction.